First records of Callibaetis radiatus and C. viviparus (Ephemeroptera: Baetidae) for Colombia - Vinasco-Mondragón, Andrés Felipe; Zúñiga, María Del Carmen Zúñiga (Revista Colombiana de Entomología, 2016)
The genus Callibaetis is broadly distributed in South America. Although it was itemized to Colombia, specific level reports were unknown. In the current study, the presence of Callibaetis radiatus and C. viviparus is being documented for the first time in the country, however, C. radiatus had already been documented in Argentina, Brazil and Paraguay while C. viviparus was reported in Brazil, only. This study is expanding the range of distribution of the two species up to the North of the Andean States.